THE EFFECT OF COMBINATION SLUDGE, HUSK CHARCOAL, COMPOST, AND NPK FERTILIZER ON THE GROWTH SWEET CORN - Fitriyani, Indri Hapsari; Widyastuti, Rahayu; Aprilianti, Nabila (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
The spice and seasoning industry produce sludge waste that has the potential to pollute the environment if not managed properly. This waste contains nutrients and organic matter, making it a potential soil conditioner for sweet corn cultivation; however, its use must be combined with other materials such as rice husk charcoal and compost. This study aims to determine the effectiveness of combining sludge, compost, husk charcoal, and NPK fertilizer on the growth and productivity of sweet corn. This study was conducted at the Cikabayan Experimental Farm using a Randomized Block Design (RBD) with five levels of sludge application: (1) 100% sludge (S1H2), (2) 75% sludge (S2H2), (3) 50% sludge (S3H2), all treatments were combined with husk charcoal (75%), compost (30%), NPK fertilizer (75%), urea (100%), (4) PB (NPK 100%), and (5) Control (no treatment). Each treatment was repeated three times, resulting in 15 experimental units. The results showed that the S2H2 treatment yielded the best results for all plant growth parameters, such as plant height, stem diameter, and all generative parameters. The S1H2 combination yielded the best results for soil chemical and biological characteristics, including pH, organic carbon, total nitrogen, total microbes, and total fungi. The S1H2 combination also yielded the best results for corn plant productivity at 5.30 tons/ha. The combination of organic matter and NPK fertilizer application is highly efficient as it reduces NPK fertilizer use by 25%.